2020
DOI: 10.3390/genes11121403
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance Profiling of Anopheles coluzzii and Anopheles gambiae Populations in the Southern Senegal: Role of Target Sites and Metabolic Resistance Mechanisms

Abstract: The emergence and spread of insecticide resistance among the main malaria vectors is threatening the effectiveness of vector control interventions in Senegal. The main drivers of this resistance in the Anopheles gambiae complex (e.g., An. gambiae and Anopheles coluzzii) remains poorly characterized in Senegal. Here we characterized the main target site and metabolic resistances mechanisms among the An. gambiae and An. coluzzii populations from their sympatric and allopatric or predominance area in Senegal. Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 65 publications
3
23
1
Order By: Relevance
“…coluzzii especially in An . gambiae s.s. populations from the south-eastern part of the country [ 20 , 32 ]. The low frequency of Vgsc-1014F observed in An.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…coluzzii especially in An . gambiae s.s. populations from the south-eastern part of the country [ 20 , 32 ]. The low frequency of Vgsc-1014F observed in An.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, Senegal has undertaken large up-scaling of pyrethroid-based vector control interventions, mainly through universal the coverage of LLIN and targeted IRS using pyrethroids in selected Senegalese health districts between 2007 and 2010 [ 18 ]. However, several reports of pyrethroid resistance amongst natural population of malaria vectors [ 14 , 19 , 20 , 21 ], could compromise the gain obtained. Moreover, although the co-occurrence of both Vgsc-1014F and Vgsc-1014S has been extensively reported from several wild populations across diverse ecological zones of the country [ 14 , 20 , 21 ], their evolutionary history and dynamic in the country remain unclear and under-investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sinensis in China and Southeast Asian countries [47]. In a recent study carried out by Yan et al, several genes have been identified which confer permethrin resistance to Culex pipiens quinquefasciatus, particularly, 2 CCEs, 6 GSTs, and 7 P450s gene were highly expressed [49].…”
Section: Metabolic Resistancementioning
confidence: 99%
“…determinants and point mutations associated with insecticide resistance in various insect vectors[18,40,43,45,46,[48][49][50][51][52][53][54][55][56][57][58].…”
mentioning
confidence: 99%